The spatial distribution relationship between mesoscale eddies and chub mackerel and its preliminary analysis of causes in the Northwest Pacific Ocean - Fan, Xiumei; Cui, Xuesen; Yang, Shenglong; Tang, Fenghua (Frontiers in Marine Science, 2025)
Chub mackerel (Scomber japonicus) is a commercially important small pelagic fish species whose distribution is strongly influenced by marine environmental conditions. Mesoscale eddies, which are widespread in the Northwest Pacific Ocean, alter the spatial patterns of local environmental variables, thereby affecting the distribution of chub mackerel. This study analyzed fishery production data of chub mackerel in the Northwest Pacific, concurrent mesoscale eddy data, and oceanographic environmental datasets. Spatial comparisons between catch distributions and eddy polarity revealed distinct southwest-northeast-oriented cyclonic eddy zones within fishing grounds. Cyclonic eddy zones were located north of anticyclonic eddy zones, with catches predominantly distributed between these zones and skewed toward cyclonic eddies. Higher catch densities were observed near cyclonic eddies compared to anticyclonic eddies, with elevated yields both inside and along the edges of cyclonic eddies. In contrast, anticyclonic eddies exhibited higher catches along their peripheries but lower values within their cores. Spatial clustering analysis using Moran’s Index and hotspot detection via the General G Index revealed statistically significant aggregation of chub mackerel catches in the southern-central regions of cyclonic eddies and the northwestern margins of anticyclonic eddies (p<0.01). The distribution characteristics of catch yields within eddy-affected areas exhibit notable similarities with environmental variable patterns. GAM modeling revealed significant correlations between chub mackerel distribution in these mesoscale eddy regions and environmental variables, with anticyclonic eddies explaining 32.8% and cyclonic eddies accounting for 47.2% of the deviance explained rate. These findings provide valuable insights into the mechanisms underlying mesoscale eddy impacts on mackerel distribution, which crucially contribute to the sustainable management and conservation of mackerel resources.